Multistep Knowledge Transfer in Multinational Corporation Networks: When Do Subsidiaries Benefit From Unconnected Sister Alliances?. (March 2020) - Faems, Dries; Bos, Brenda; Noseleit, Florian; Leten, Bart
In this paper, we explore under which conditions subsidiaries of multinational corporations can benefit from the external networks of sister subsidiaries in terms of new knowledge generation. We focus on the phenomenon of unconnected sister alliances—that is, alliances of sister subsidiaries with whom the focal subsidiary lacks a recent history of internal R&D collaboration. Whereas unconnected sister alliances provide knowledge recombination opportunities for the focal subsidiary, realizing them is challenging because of particular knowledge transfer frictions. In this paper, we theorize on how particular conditions (i.e., headquarters proximity, knowledge overlap, size of focal subsidiary's own alliance network) influence the strength of these frictions, resulting in hypotheses on how these conditions moderate the relationship between the number of unconnected sister alliances and the generation of new knowledge by focal subsidiaries. We rely on a panel data set of 2, 258 R&D subsidiaries belonging to 118 firms in the pharmaceutical industry to empirically test our hypotheses. Jointly, our findings enrich our current theoretical understanding of how different types of external linkages and their interactions shape subsidiaries' generation of new knowledge. We also illuminate the opportunities and challenges that multistep knowledge transfer processes entail.